Experimental investigation of the turbulent density – Far-field sound correlations in compressible jets. Issue 4 (July 2018) - Mercier, Bertrand; Castelain, Thomas; Bailly, Christophe
Jet mixing noise is experimentally investigated by means of cross-correlations between density fluctuations inside the turbulent jet flow and the far-field acoustic pressure. The time-resolved density fluctuations are measured by an experimental device based on Rayleigh scattering, which is mounted in the large anechoic wind tunnel of Ecole Centrale de Lyon. An original signal processing developed in a previous study is implemented for the photon counting, combined with the use of a single photomultiplier to remove shot noise. A high-speed subsonic jet and a perfectly expanded supersonic jet with a subsonic convective velocity are considered to characterize mixing noise sources. In order to go beyond the classical Fourier analyses, conditional cross-correlations are determined, and the signature of turbulent events linked to the noise emission in the downstream direction is extracted.